Interventions for prevention of Nipah virus transmission and infection in Bangladesh - Ashraf, Lamisa (Archives of Community Medicine and Public Health, 2020)
Nipah virus (NiV) infections have been prevalent in Bangladesh since 2001. This virus is usually transmitted from infected bats to humans, and from humans to humans in Bangladesh. The most common source of transmission of Nipah virus in Bangladesh is through the consumption of a drink made from raw date palm sap that has been contaminated by infected bats’ saliva or urine. This paper describes several interventions to prevent the transmission of Nipah virus, namely, behavior change interventions, surveillance of cases, and quarantine of infected individuals. This paper also briefly touches upon the recent advancements in the development of vaccines against Nipah virus. Behavior change interventions, namely educating individuals at risk, either in person or through mass media, is an effective way of spreading awareness about and preventing the transmission of NiV. Surveillance systems can help early case detection; however, this might yield misleading numbers if there is underreporting of cases. Quarantine of infected persons is likely to be expensive and would require the presence of extensively trained personnel. Vaccines against NiV are currently being developed and the results from animal tests have been promising. In Bangladesh, given the lack of resources, behavior change intervention would be the most cost-effective way of preventing the spread of NiV, compared to routine surveillance and/or quarantine of cases. Therefore, in order to prevent NiV infections, focus should be geared towards behavior change communication through education about the transmission of NiV, provided to those living in high-risk areas of Bangladesh.